CD40L expression in plasma of volunteers following LPS administration: A comparison between assay of CD40L on platelet microvesicles and soluble CD40L. (25th June 2014) - Mobarrez, Fariborz; Sjövik, Carolina; Soop, Anne; Hållström, Lars; Frostell, Claes; Pisetsky, David S.; Wallén, Håkan
Abstract: CD40 ligand (CD40L) is a transmembrane protein that is mainly expressed on activated T cells and platelets. This protein, however, may also be shed from cells and circulate in the blood in a soluble form. "Soluble CD40L" has attracted interest as a biomarker as it can interact with CD40 and elicit cellular responses involved in the pathophysiology of various thrombotic and inflammatory conditions. As platelets can release microvesicles following activation, we investigated the expression of CD40L on circulating microvesicles as well as CD40L in plasma, in an experimental model of inflammation in healthy volunteers (i.e., intravenous lipopolysaccharide administration). We studied CD40L quantified as CD40L-positive platelet microvesicles by flow cytometry, and as CD40L in plasma ("soluble CD40L") by an ELISA. Results of these studies showed that levels of CD40L exposed on platelet microvesicles were significantly increased after lipopolysaccharide administration. ELISA measurements of CD40L in plasma ("soluble CD40L") did not show any significant increase in plasma levels over time. Separation of soluble and vesicle-bound CD40L by high-speed centrifugation indicated that the ELISA can also detect CD40L on microvesicles, as a trend toward increased concentrations were observed in the pellet of high-speed centrifuged samples (i.e., in samples in which microvesicles are enriched). Together, these findings suggest that platelet microvesicles are a source of CD40L in the circulation and that CD40L exposure on platelet microvesicles increases following experimentally induced inflammation. Our data also suggest that determining levels of CD40L on microvesicles in plasma samples may provide a more sensitive detection of changes in CD40L expression than measurement of "soluble CD40L" in plasma with an ELISA. In addition, information regarding the cellular source of CD40L can be obtained with a flow cytometry-based microvesicle assay in a way not possible with an ordinary ELISA.